Numerical solution of Fredholm integral equation of the first kind with degenerated kernel by using Hermite polynomial - Talhat I.Hassan; Najmaddin A.Sulaiman (College of Education for Pure Sciences, 2006)
In this paper we used Hermite polynomial with Galerkin , collocation and least square methods for solving fredholm integral equations of the first kind (F.I.E.F.K) with degenerated kernel .The algorithms and computer applications of the algorithms are given for the methods which have tested through numerical exaples and compared the results with exact solutions as indecated in tables (1,2,3,4), (used Matlab programmong in this work).